A study of percutaneous k-wire fixation of supracondylar fracture in children in a tertiary care institute - Narendra Kumar (International Journal of Medical Research and Review, 2016)
Introduction: In orthopaedics practice Supracondylar fracture of humerus is the commonest injury around elbow in children during fall on the outstretched hand. The complications of this injury are many like pain, deformity and permanent restriction of movement however if due care is taken and early treatment is started, excellent results are seen. Various treatment modalities are used for treating these fractures. Closed reduction and percutaneous pinning is a useful technique to manage this condition.Methods: Thirty five cases with Gartland type III supracondylar humeral fractures were treated with closed reduction and percutaneous lateral pin fixation with Kirschner wire and followed up for 12 months.Results: Results were excellent in 30 patients and good in 4 patients according to Flynn’s criteria. There was only one patient with poor results. Post-operatively, one patient sustained ulnar nerve injury. Two patients got pin tract infection which were superficial and healed after removing pins and antibiotics. Union was seen in all patients at the 2-3 weeks post-operatively before removing the K-wires.Conclusion: It is concluded that closed reduction and lateral pin fixation is a safe and effective treatment modality for management of supracondylar fractures with minimum complication rate.